Healthcare Professionals Perspectives on Discharge Planning for Patients with Mental Illness - Sari, Hasmila; Keliat, Budi Anna; Sahar, Junaiti; Susanti, Herni; Junus, Kasiyah (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2024)
Introduction: Discharge planning is transferring a patient to a different level of care to improve continuity of care by bridging the gap between hospital and community care. This study aimed to explore the perspectives of healthcare professionals involved in discharge planning for patients with mental illness. Method: This research used qualitative methods with a phenomenological approach. Ten participants were selected using a purposive sampling method, with inclusion criteria healthcare professionals involved in the discharge planning process for patients in psychiatric hospitals, had worked in the service for at least 5 years, and provided direct or indirect services to patients. Data were collected through in-depth interviews using interview guides, recording devices, and field notes. Data were analyzed using thematic analysis. Results: The study identified four themes related to discharge planning preparation for patients with mental illness perceptions of roles and experiences in discharge planning, internal and external barriers in discharge planning, internal and external support in discharge planning and expectations for the continuity of discharge planning. Conclusions:  The findings indicate that there are still significant disparities in the way that discharge planning for patients with mental illness is implemented in different mental health service settings. These study findings are intended to serve as a further source of information to develop a discharge planning system that integrates patients with mental illnesses from the hospital into the community.